2022
DOI: 10.1002/adfm.202206094
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Inch Wafer‐Scale Exfoliation of Hexagonal Boron Nitride Films Fabricated by RF‐Sputtering

Abstract: A film stripping method that allows for liquid phase exfoliation assisted by spin coating polymethyl methacrylate has been investigated, resulting in a two‐inch hexagonal boron nitride (hBN) film to be fully stripped and then transferred. A number of key factors that can influence the stripping and the transferring process of the films grown by sputtering have been systematically analyzed, including different solutions, different concentration of solution and different thickness of films. The morphology and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Furthermore, the h-BN/B 1– x Al x N heterojunction with a centimeter scale area was first constructed based on the mature stripping technology of 2 in. wafer-scale h-BN in our previous study . The obvious rectification properties suggested that the low formation energy of heterojuncion existed in h-BN/B 0.89 Al 0.11 N heterojunction.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Furthermore, the h-BN/B 1– x Al x N heterojunction with a centimeter scale area was first constructed based on the mature stripping technology of 2 in. wafer-scale h-BN in our previous study . The obvious rectification properties suggested that the low formation energy of heterojuncion existed in h-BN/B 0.89 Al 0.11 N heterojunction.…”
Section: Introductionmentioning
confidence: 68%
“…wafer-scale h-BN in our previous study. 27 The obvious rectification properties suggested that the low formation energy of heterojuncion existed in h-BN/B 0.89 Al 0.11 N heterojunction.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Li et al 155 further realized the wafer-level continuous exfoliation of h-BN on the basis of the previous magnetron sputtering preparation of h-BN films and obtained the wafer-level transfer of h-BN films. Factors affecting the exfoliation and transfer of continuous thick films grown by sputtering were analyzed, including different exfoliation solutions (acid/base/deionized water), different solution concentrations (0.1−6 mol/L), and different film thicknesses (50−120 nm).…”
Section: 412mentioning
confidence: 99%